Triple G-C-T base-coded self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications - Singh, Dharmendra; Gone, Nilu V.; Bandi, Kiran; Davis, Disiya; Nair, Kiran Sukumaran; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2025)
We report self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications. These nucleobase monomers are adorned with nature-inspired triple G-C-T nucleobases featuring three recognition sites: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Using readily accessible starting materials, these monomers can be synthesized in excellent yields, making them good choices for diverse applications. Their unique structural features, coupled with their water solubility, may offer exciting opportunities for the creation of new biomaterials.